2023
DOI: 10.1093/jas/skad195
|View full text |Cite
|
Sign up to set email alerts
|

Late gestational nutrient restriction in primiparous beef females: nutrient partitioning among the dam, fetus, and colostrum during gestation

Abstract: Fall-calving primiparous crossbred beef females [body weight (BW): 451 ± 28 (SD) kg; body condition score (BCS): 5.4 ± 0.7] were allocated by fetal sex and expected calving date to receive either 100% (control; CON; n = 13) or 70% (nutrient restricted; NR; n = 13) of metabolizable energy and metabolizable protein requirements for maintenance, pregnancy, and growth from d 160 of gestation to calving. Heifers were individually-fed chopped poor quality hay and supplemented to meet targeted nutritional planes base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 73 publications
(119 reference statements)
1
22
0
Order By: Relevance
“…We reported that calf birth weight was not affected ( P = 0.72; 29.9 vs. 30.7 ± 1.7 kg) by late gestational nutritional plane ( Redifer et al, 2023 ). With CON and NR dams combined, calf birth weight had a moderate relationship ( r = 0.40 to 0.53; P ≤ 0.05) with milk weight on days 21, 42, 63, 84, and 105 of lactation, but calf birth weight was not correlated ( r = 0.30; P = 0.14) with milk weight on day 147 of lactation.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…We reported that calf birth weight was not affected ( P = 0.72; 29.9 vs. 30.7 ± 1.7 kg) by late gestational nutritional plane ( Redifer et al, 2023 ). With CON and NR dams combined, calf birth weight had a moderate relationship ( r = 0.40 to 0.53; P ≤ 0.05) with milk weight on days 21, 42, 63, 84, and 105 of lactation, but calf birth weight was not correlated ( r = 0.30; P = 0.14) with milk weight on day 147 of lactation.…”
Section: Resultsmentioning
confidence: 82%
“…We reported that nutrient restricted dams weighed 63.6 kg less and were 2.0 BCS lower than controls post-calving, but calf BW and size at birth were not affected by late gestational nutrient restriction ( Redifer et al, 2023 ). Nutrient restricted dams produced 40% less colostrum, yet it was generally more concentrated so that total colostral nutrients and immunoglobulins, except lactose, were similar ( Redifer et al, 2023 ).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations